Penggunaan Lampu Tenaga Surya untuk Penerangan Jalan di Dusun Palintang, Desa Cipanjalu - Heri Andrianto; Dedi Anderias Bailao (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
The absence of adequate street lighting due to limited access to the national electricity grid (PLN) not only diminishes residents' sense of security and comfort but also increases the risk of crime and accidents, while obstructing social and economic activities. Although Dusun Palintang, located in Cipanjalu Village, Cilengkrang Subdistrict, Bandung Regency, is already connected to the PLN electricity network, several areas remain without proper street lighting, posing safety hazards for the community, particularly at night. This community service project aims to enhance public safety and support nighttime activities by installing energy-efficient and effective solar-powered street lighting. The implementation method consists of four stages: initial observation, fabrication of streetlight poles, installation of solar-powered streetlights, and training sessions for local residents on the operation and maintenance of the lighting system, including how to adjust the lighting modes. The solar-powered streetlights have been successfully installed and are functioning effectively. This initiative has contributed significantly to improving the quality of life for the local community by providing safer and more comfortable conditions for evening activities.